Distribution and clinical characteristic of malaria patients in Weoe Public Health Center, Malaka District, East Nusa Tenggara in 2019 - Maria Seraphine Agusta; Ni Putu Inna Ariani; Christianus Heru Setiawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Malaria remains a health problem in Indonesia including in East Nusa Tenggara (ENT) Province where its incidence is high. Weoe Public Health Center located in Malaka District, ENT Province has an important role as the front-line in the malaria control. The high number of malaria cases in this area may induce an economic burden due to unproductiveness at workplaces even death. This study aimed to overview the distribution and clinical characteristics of malaria patients in Weoe Public Public Health Center, Malaka District. This was a descriptive cross sectional study with saturated sampling method using secondary data of patient’s medical record from January-December 2019. Malaria patients treated at the Weoe Public Health Center from eight villages were selected in this study. The data of the time of ill, patient’s residence, gender, age, complaints, temperature, type of malaria, therapy, treatment results, and follow up blood smear tests result were collected. Among 815 patients suspected malaria, 198 (24.3%) were confirmed malaria positive caused by Plasmodium falciparum (41.4%) and P. vivax (58.6%). The highest cases occurred in February which reached 36.4% of the total cases. The highest incidence of malaria was found in Weoe Village (2.33%), dominated by male patients (57.6%), and mostly occurred at age 6-12 years (29.3%). Patients presented with fever (100%) followed by non-classical malaria complaints such as nausea and vomiting (46%), headache (33%), chills (30.8%), and flu symptoms (14.1%). All malaria patients were treated with combination of dihydroartemisinin-piperaquine (DHP) and primaquine (PQ) with a 100% cure rate and follow up blood smear test are negative from malaria parasite.